Assessment of the acceptable range of aircraft lateral deviations on the approach phase - Харченко, В. П.; Тапіа, К. М.; Швець, О. В. (Proceedings of National Aviation University (archive), 2013)
The dependence of the acceptable range of aircraft lateral deviations from landing trajectory by appropriate aircraft approach category, at which it is possible its successful completion, is considered